Extension of the Shelf-Life of Fresh Pasta Using Chickpea Flour Fermented with Selected Lactic Acid Bacteria - Schettino, Rosa (Microorganisms, 2020)
Fresh pasta is subjected to rapid spoilage, mainly due to the metabolic activity of bacteria, yeasts, and especially molds, which negatively affect the sensorial characteristics and the safety of the product. In this work, chickpea flour was fermented with selected lactic acid bacteria, characterized in terms of the antifungal activity, and used to fortify fresh semolina pasta. Pasta was characterized and subjected to a long period of storage after being artificially inoculated with Penicillium roqueforti. Conventional fresh semolina pasta, produced with or without calcium propionate addition, was used as a reference. The water/salt-soluble extract from chickpea sourdough exhibited antifungal activity towards a large spectrum of molds. Its purification led to the identification of ten potentially active peptides. Besides the high content of dietary fibers (4.37%) and proteins (11.20%), nutritional improvements, such as the decrease of the antinutritional factors concentration and the starch hydrolysis index (25% lower than the control) and the increase of the protein digestibility (36% higher than the control), were achieved in fresh pasta fortified with the chickpea sourdough. Inhibition of the indicator mold growth during a 40-day storage period was more effective than in pasta added to calcium propionate.